Theatrum Arbitri : theatrical elements in the Satyrica of Petronius - Panayotakis, Costas. (Mnemosyne, Supplements, 1995)
Theatrum Arbitri is a literary study dealing with the possible influence of Roman comic drama (comedies of Plautus and Terence, theatre of the Greek and Roman mimes, and fabula Atellana ) on the surviving fragments of Petronius' Satyrica . The theatrical assessment of this novel is carried out at the levels of plot-construction, characterization, language, and reading of the text as if it were the narrative equivalent of a farcical staged piece with the theatrical structure of a play produced before an audience. The analysis follows the order of each of the scenes in the novel. The reader will also find a brief general commentary on the less discussed scenes of the Satyrica , and a comprehensive account of the theatre of the mimes and its main features.